Resolución de problemas en matemática - ABRANTES, Paulo; BARBA, Carme; BATLLE, Isabel; BOFARULL, María Teresa; COLOMER, Trini; FUENTES, María Teresa; GARCIA GIMENES, Juan Emilio (GRAO, 2002)
Otros autores: GARCIA MADRUGA, Juan Antonio; MARTI, Eduardo; RAMOS, Nuria; RECARENS, Elisa; SEGARRA, Lluís; SERRA, Teresa; TORRA, Monserrat